OPTICAL APPROACHES IN INFORMATION TECHNOLOGY - (:unkn) unknown (My University, 2022)
The issues of fiber-optic lines and components of fiber-optic transmission systems are outlined, the principles of operation of systems with open atmospheric communication channels are described